Generation and characterization of nanobubbles for heat transfer applications. (2021) - Senthilkumar, G.; Purusothaman, M.; Rameshkumar, C.; Joy, Nivin; Sachin, S.; Siva Thanigai, K.
Abstract: This paper specifies the generation of nanobubbles in Heat Transfer Fluid (HTF) using Mechanical stirring process and their influence in thermo physical properties of HTF. Therminol 66 is investigated as HTF in this experimental work. Nanobubbles are of diameter less than 200 nm. Thermal conductivity, viscosity, surface tension, Flash and fire point are studied in this research. The comparison is made between above mentioned properties for normal HTF and Nanobubbled HTF. The results obtained for nanobubbled HTF showed that an increase in 11% thermal conductivity. The fire point increased up to 10% in Nanobubbled HTF compared to normal HTF. The flash point also increased by 46% in Nanobubbled HTF as compared to normal HTF. The viscosity increased by 35%in Nanobubbled HTF compared to normal HTF. But the surface tension remains same in both normal HTF and Nanobubbled HTF. The capillary effect is reduced to 20% in Nanobubbled HTF compared to normal HTF.